Razones para una nueva división cronológica de la historia antigua de los mayas - Rivera Dorado, Miguel (Revista Española de Antropología Americana, 2003)
The science of the ancient Maya had changed very notably in the last thirty years, but the periods in the historical sequence accepted by the specialists are the same. In this paper I propose news possibilities on the matter.